Jejak Sejarah Alsara Ulu Di Lubuklinggau Warisan Literasi Masyarakat Uluan - Rahayu, Nyimas; Wiji Rahayu; Indri Maya Sari; Zandia Murti; Yeni Asmara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to describe the historical traces, development, function, and preservation efforts of the Ulu script as a literary heritage of the Uluan community in Lubuklinggau City. The study employed a qualitative approach with a descriptive-historical method. Data collection was conducted through literature review utilizing various sources, such as books, scientific journal articles, research reports, and documents discussing the history, literacy, and preservation of the Ulu script. Data analysis was conducted descriptively and qualitatively through the processes of classification, interpretation, and synthesis of information from various sources, while data validity was strengthened using source triangulation. The results indicate that the Ulu script is a traditional writing system that developed in the upper reaches of the Musi River from around the 9th century until reaching its peak in the 13th century AD. This script serves as a medium for recording local history, customary law, religious teachings, literature, and traditional medical knowledge, thus demonstrating the development of the Uluan community's literacy tradition. However, developments, globalization, and the dominance of the Latin script have caused the use of the Ulu script to decline and become less familiar to the younger generation. Various preservation efforts have been undertaken through education, literacy training, manuscript documentation, digitization, and cultural outreach. This study concludes that the Ulu script is a cultural heritage with high historical, educational, and local identity value. Therefore, synergy between the government, educational institutions, cultural communities, and the community is needed to ensure its continued preservation in the digital age. Keywords: Cultural Heritage, Cultural Preservation, Literacy, Uluan Community, Ulu Script.